Cellular composition characterizing postnatal development and maturation of the mouse brain and spinal cord - Fu, Y.; Rusznak, Z.; Herculano-Houzel, S.; Watson, Charles; Paxinos, G. (Springer, 2013)
The process of development, maturation, and regression in the central nervous system (CNS) are genetically programmed and influenced by environment. Hitherto, most research efforts have focused on either the early development of the CNS or the late changes associated with aging, whereas an important period corresponding to adolescence has been overlooked. In this study, we searched for age-dependent changes in the number of cells that compose the CNS (divided into isocortex, hippocampus, olfactory bulb, cerebellum, ‘rest of the brain’, and spinal cord) and the pituitary gland in 4–40-week-old C57BL6 mice, using the isotropic fractionator method in combination with neuronal nuclear protein as a marker for neuronal cells. We found that all CNS structures, except for the isocortex, increased in mass in the period of 4–15 weeks. Over the same period, the absolute number of neurons significantly increased in the olfactory bulb and cerebellum while non-neuronal cell numbers increased in the ‘rest of the brain’ and isocortex. Along with the gain in body length and weight, the pituitary gland also increased in mass and cell number, the latter correlating well with changes of the brain and spinal cord mass. The majority of the age-dependent alterations (e.g., somatic parameters, relative brain mass, number of pituitary cells, and cellular composition of the cerebellum, isocortex, rest of the brain, and spinal cord) occur rapidly between the 4th and 11th postnatal weeks. This period includes murine adolescence, underscoring the significance of this stage in the postnatal development of the mouse CNS.